How The Role of Celebrity Cadres in The Digital Political Campaign of The National Mandate Party in 2024 Election - Subekti, Dimas; Nasuhaidi, Nasuhaidi; Pasaribu, Ian (Universitas Pancasakti, 2024)
This research explains the role of celebrities in the digital political campaign conducted by the National Mandate Party (PAN) in the 2024 election. This research uses a qualitative method with a case study approach. Furthermore, this research also used NVIVO 12 plus tools in analyzing data. The findings in this study explain that PAN celebrity cadres have two dominant roles in digital political campaigns, namely creating creative content and also mobilizing fan bases. These celebrities use their personal social media capital to conduct political campaigns, both by creating short videos and memes. Likewise, in gathering the support of their fans in the form of building an active online community. Furthermore, Instagram is the most dominant social media used for political campaigns by these celebrities. Then, TikTok social media is also the second dominant one used for political campaigns. Then, there are YouTube and Facebook which are also used for political campaigns. The implications of this research explain that today's digital power can be used effectively in political campaign strategies that have a positive impact on party votes in elections.